MUTRASHMARI (UROLITHIASIS): A CASE SUCCESSFULLY TREATED WITH GOKSHURADI GUGGULU - Aaditya B. Shah; Poonam Mohod; V. C. Deep; Gopesh Kumar Sharma (International Journal of Ayurveda and Pharma Research, 2020)
Urolithiasis is a process of resembling stone in urinary tract (In Kidney/Ureter/ Bladder). It is also known as Kidney stone disease. In Ayurvedic literature Urolithiasis is refereed as Mutrashmari. Urolithiasis is very common disease in India, men are more affected than woman and its recurrent rates are very high. The common symptoms of Urolithiasis are Intermittent dull or colicky flank Pain, Painful or Burning urination, Cloudy or foul-smelling urine, blood in the urine and Nausea/Vomiting. In modern system, extracorporeal shock wave lithotripsy, Percutaneous Nephrolithotomy, Retrograde Intrarenal Surgery and Laparoscopic Ureterolithotomy are the surgical option available for big size kidney stone. However, there is no proper internal medication available for small size Urolithiasis but causative factors, clinical features, type and prognosis of Mutrashmari are elaborately described in classical text of Ayurveda. Gokshuradi Guggulu is commonly used herbal medicine in Ayurveda for urinary disorders. Small kidney stones with a diameter of less than 5 millimeters are often flushed out in the urine. But here in this case 4mm kidney stone was creating pain and not flushing out even after more than a week. After medication it was found that the stone easily flushed out in the urine with the help of Gokshuradi Guggulu.